Determination of the Optimum Crown Pillar Thickness between Open Pit and Block Caving - Ezzeddin Bakhtavar; Kazem Oraee; Kourosh Shahriar (International Conference on Ground Control in Mining, 2010)
"In this paper, a relationship between dependant parameters and the crown pillar thickness is first introduced. This relationship defines geotechnical problems caused by thin pillars and economic considerations created by pillars that are thicker than the optimum size. For this purpose, a dimensional analysis as an effective physico-mathematical tool was used. This technique restructures the original dimensional variables of a problem into a set of dimensionless products using the constraints imposed upon them by their dimensions. A model is hence introduced that calculates the optimum pillar thickness. The relationship introduced here and the method applied can be used by mining engineers in all situations where a combined open-pit and block caving method is deemed to be the most appropriate mining method.INTRODUCTIONMany deposits can be mined entirely with the open-pit method; others must be worked underground from the very beginning. In addition, there are the near-surface deposits with considerable vertical extent. Although they are initially exploited by the open pit method, there is often a ""transition depth"" where decision has to be made about changing to underground methods.Some of the biggest open-pit mines worldwide will reach their final pit limits in the next 10 to 15 years. Furthermore, there are many mines planning to change from open-pit to underground mining due to increasing extraction depths and environmental requirements. In this way, it is likely that block and/or panel caving will enable the operations to continue achieving a high production rate at low costs as an underground method (Bakhtavar et al., 2009).In these cases, it is often necessary to consider a crown pillar beneath the transition depth (open-pit floor) before starting an underground caving stope method (Figure 1).There are generally two kinds of crown pillar: a ""surface crown pillar"" and ""crown pillar between open-pit and underground mining."" In general, they both play the similar role in mining. Since the primary purpose of a surface crown pillar is to protect surface land users, the mine, and those working in it from inflows of water, soil, and rock; it is vital that the surface crown pillars remain stable throughout their life. When a crown pillar could potentially remain between open-pit and underground mining it is specially proposed to prevent water entering from the open-pit floor into the stope, as well as to reduce open-pit wall and floor caving."